Trends in FDI Inflows to Russia in the Time of Political Tension - Mińska-Struzik, Ewa; Nowara, Wanda (Studia Oeconomica Posnaniensia, 2017)
The paper presents the outcomes of the analysis of development trends in FDI inflow to Russia, concerning its geographical and sector structure in the years 2010-2014. The authors identify the examples of countries, sectors and companies which have decided to increase investment despite the political crisis.